2016
DOI: 10.21859/jne-05045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Belief Model Education on the Participation of Rural Women in Papsmear Test

Abstract: Introduction: Cervical cancer is one of the most prevalent cancers in females. Pap smear test is an effective screening program; however, it is not conducted very frequently. The purpose of this article was to present findings on the effect of health belief model education on women's participation in Pap smear examination. Methods: The study included a convenience sample of asymptomatic females aged 20 years and older, who were living in Sarvabad. Overall, 180 subjects were selected and randomly divided to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…[ 23 24 ] Five trials did not report any attempt to blind assessors to treatment assignment[ 3 19 23 25 26 ] and five study did not blind. [ 22 24 27 28 29 ] In 2 trials, the participants/providers, or both were blinded to treatment allocation. [ 20 21 ] Eight trials did not provide information about the number of participants allocated to groups at randomization[ 3 19 24 25 26 27 28 29 ] and four trials reported attrition bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 23 24 ] Five trials did not report any attempt to blind assessors to treatment assignment[ 3 19 23 25 26 ] and five study did not blind. [ 22 24 27 28 29 ] In 2 trials, the participants/providers, or both were blinded to treatment allocation. [ 20 21 ] Eight trials did not provide information about the number of participants allocated to groups at randomization[ 3 19 24 25 26 27 28 29 ] and four trials reported attrition bias.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 24 27 28 29 ] In 2 trials, the participants/providers, or both were blinded to treatment allocation. [ 20 21 ] Eight trials did not provide information about the number of participants allocated to groups at randomization[ 3 19 24 25 26 27 28 29 ] and four trials reported attrition bias. [ 20 21 22 23 ] In 12 studies, the inclusion and exclusion criteria and selective outcome were clearly defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations